A Combinational Prediction Model for Transverse Crack of Asphalt Pavement - Zhang, Chen; Wang, Hainian; Yang, Xu; You, Zhanping (KSCE Journal of Civil Engineering, 2018)
© 2018, Korean Society of Civil Engineers. Reliable transverse crack prediction can benefit the design and maintenance and improve the reliability of field investigation for asphalt pavement in permafrost regions of Qinghai-Tibet plateau. This study adopted the crack prediction model in the newly developed pavement design method named Pavement ME Design (PMED) and the modified grey predictive model (GM (1, 1)) to predict the transverse crack of asphalt pavement in permafrost regions. The complementary advantages for the two models based on the weight distribution theory were discussed, and a combined prediction model (PME-DGM combination model) taking account into region characteristics was developed. Finally, the applicability of combined prediction model was analyzed. The result showed that, the predictive accuracy of PME-DGM combination model established by the error sum of squares reciprocal method was the highest, the best weight allocations for each sub-model were LNCH = 0.601 and LDGM = 0.399, and the combination model can be applied in the permafrost region involved in this paper; The combination model is more appropriate in predicting the development trend of transverse crack of project-level asphalt pavement in permafrost regions; For PMED predictive model, this study raised a modified method base on a third-party model (DGM (1,1), and the result showed that the method worked well in the permafrost region of Qinghai-Tibet plateau.